Effects of structured home-based exercise program on depression status and quality of life in burn patients - ÜNLÜ, BEGÜM; YURDALAN, SAADET UFUK (ELSEVIER SCI LTD, 2018)
Background: Burns can cause life-threatening injuries and severe limitations. This study aimed to evaluate the effects of the structured home-based exercise program on depression status and quality of life in burn patients. Materials and methods: This study was carried out in the Wound and Burn Treatment Department of University of Health Sciences, Dr. Lutfi Kirdar Kartal Education and Research Hospital, Istanbul. Thirty burn patients voluntarily participated in this study. Patients' demographic data such as burn area and grade, percentage, type, number of grafts, and duration of hospitalization were recorded. The quality of life was evaluated using the Short Form-36(SF-36), and depression status was evaluated using Beck Depression Inventory (BDI). The home-based exercise program was defined by the clinical physiotherapist on the day when the patient was discharged. The home-based exercise program was applied for 3 weeks. Evaluations were performed at discharge and repeated after 3 weeks at the end of the exercise program. Results: Of the 30 patients who completed the study (age range, 21-61 years; mean,34.9 +/- 12.99 years), 96.7% (n=29) were male and 3.3% (n=l) were female. A statistically significant difference was observed between BDI and SF-36 scores before and after the home-based exercise program (p<0.05). BDI scores decreased after the home-based exercise program, whereas SF-36 scores increased. Conclusion: Our study concludes that burn patients who underwent the structured home-based exercise programs attained acceleration of their physical, social, and psychological integrity. Thus, establishing a structured home-based exercise program according to the burn type and clinical course should be continued. (C) 2018 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Burn; physiotherapy; Depression; Quality of life; Exercise; INVENTORY-II; PSYCHOMETRIC PROPERTIES; PULMONARY-FUNCTION; HEALTH; CHILDREN; INJURY; REHABILITATION; SYMPTOMS; ADULTS; SF-36